Profil Berpikir Kritis Siswa SMP Negeri 2 Palang Dalam Pemecahan Masalah Matematika Ditinjau Dari Gaya Belajar - Arista, Anik; Yuliastuti, Rita; Nurfalah, Edy (FKIP Unirow Tuban, 2022)
Mathematics is the science of logic, abstract objects, concepts that are equally related to each other whose reasoning is deductive. Solving mathematical problems plays a significant role in schools, where students are required to have the skills to solve mathematical problems correctly and thoroughly. In solving mathematical problems linking thinking activities, one of which is critical thinking. Based on the observations that the researchers tried when they were tutoring tutors at one of the students of SMP Negeri 2 Palang, it was found that one of the cases was about students' critical thinking in solving mathematical problems that were still lacking. This can be seen from the number of students who still have not mastered the case on questions and students tend to use the quick formula. Therefore, critical thinking skills in solving mathematical problems need to be studied further. More so seen from the different learning styles of students. For this purpose, researchers are interested in studying the case by giving the title